2019
DOI: 10.1111/jocd.12934
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin‐17 as a novel biomarker in patients with acne vulgaris

Abstract: Background Acne vulgaris is a common chronic inflammatory skin disease involving pilosebaceous units. Both innate and adaptive immunity, especially the T helper 17 pathway, may contribute to the inflammatory response in acne. Objectives We aimed at evaluation of serum interleukin‐17 (IL‐17) level in patients with acne vulgaris in order to assess its role in disease pathogenesis and its clinical significance. Methods Serum IL‐17 level was measured by an ELISA technique in 80 acne vulgaris patients and 80 appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
1
17
2
Order By: Relevance
“…[ 28 ] and Ebrahim et al . [ 7 ] lending further support to the association. However, this finding was contrary to the findings of Maulinda et al .…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…[ 28 ] and Ebrahim et al . [ 7 ] lending further support to the association. However, this finding was contrary to the findings of Maulinda et al .…”
Section: Discussionmentioning
confidence: 68%
“…Some previous reports have shown raised tissue IL-17 levels in acne patients, while few recent studies from Egypt have shown increased intralesional as well as serum IL-17 levels. [ 7 12 ] The higher serum IL-17 levels are likely due to a spill-over of increased IL-17 secretion at the disease site. The high levels in serum resulting from a disease localized to a small area of skin is reflective of the quantum of this cytokine produced at one site and emphasizes its important role in the pathogenesis of acne.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-17 and related cytokines are proinflammatory cytokines known to promote antimicrobial protective responses and barrier maintenance but also pathogenic inflammation upon chronic activation (McGeachy et al, 2019). IL-17 (Ebrahim et al, 2019) and Th17 cells (Agak et al, 2014, Kelhala et al, 2014 were reported to be associated with acne pathogenesis but their functional role in acne remains understudied.…”
Section: Introductionmentioning
confidence: 99%